Study on the evolution and prediction of fracture depth of surrounding rock in deep mining roadway based on numerical analysis and borehole detection - Li, Huaibin; Zhao, Xingdong; Dai, Bibo; Huang, Zujun; Zhu, Qiankun (Frontiers in Earth Science, 2022)
The failure of surrounding rock in deep hard rock roadway is closely related to mining disturbance. In this study, the 13# stope ramp of -767 m level (at a buried depth of 1197 m) at Hongtoushan copper mine was taken as the engineering background, a comprehensive analysis method of numerical analysis and borehole detection was put forward, and the evolution law of fracture depth of the ramp surrounding rock under the mining influence was obtained. The results show that the maximum tangential stress and fracture depth of the ramp surrounding rock on both sidewalls increase slowly at the initial mining stage. When the ore body above the ramp is mined, the maximum tangential stress and fracture depth of the ramp surrounding rock on both sidewalls increase rapidly, and the two parameters are positively correlated. Based on this, the ratio of the maximum tangential stress of the surrounding rock to the uniaxial compressive strength of intact rock (σθmax/σc) and the equivalent radius (a) of the roadway were used as parameters, and an equation for the fracture depth of the roadway surrounding rock was proposed. Through the case analysis, the results show that the proposed equation of fracture depth of the roadway surrounding rock has good prediction accuracy. This study enriches the research on the stability and failure mechanism of the roadway surrounding rock under the mining disturbance, and provides new basis for the support design of mining roadways.